Pengembangan Green Tourism Dengan Penerapan Green Financing Berbasis Kearifan Lokal Di Wilayah Kabupaten Mandailing Natal - Ar Rahmah, Rizka; Harahap, Ahmad Rizki; Hasibuan, Rahmat Putra Ahmad (Owner : Riset dan Jurnal Akuntansi, 2024)
This research aims to examine the potential for sustainable tourism development by implementing the Green Tourism and Green Financing approaches based on local wisdom in the Mandailing Natal Regency area. The primary focus of this study is to formulate strategies and implementation models that can enhance the positive impact of tourism on the environment and the local community. The research employs a qualitative methodology with a case study approach. Data is collected through in-depth interviews, field observations, and analysis of relevant documents. Additionally, a local potential mapping and sustainability analysis approach is used to identify opportunities and challenges in developing green tourism in the Mandailing Natal Regency. The findings indicate significant potential for developing green tourism in this area by leveraging local wisdom. The implementation of Green Financing has proven to provide the necessary financial support for sustainable tourism projects. Moreover, the integration of local wisdom in tourism management can create harmonious interactions between tourists and the local community, enhancing the tourist experience and positively impacting local economic development. The results of this research offer practical guidance for local governments, tourism stakeholders, and financial institutions in building sustainable green tourism in the Mandailing Natal Regency.